(untitled) (Huellas, 2018)
Large corporations, belonging to the upper circuit of urban economy, deploy expansion strategies that reconfigure ways of marketing and consumption. They articulate their actions in a banal space made up of actors with different interests, power of imposition and capacities in the use and appropriation of the territory. In the current period, the corporate use of the territory is manifested through the implementation, increasingly notorious, of the franchise system. The particular feature of this system is that it allows the installation of a market of brands that grows independently of the investment of large capitals, once these have gained notoriety in the market. Based on the Theory of Circuits of the Urban Economy (Santos, 1979), we study the characteristics acquired by the variable ‘capital’in the constitution of franchising, based on two indicators: the origin of capital and the relationships between franchisor and franchisee in commercial spaces.